Regional income inequality in Germany - Immo Frieden; Andreas Peichl; Paul Schüle (EconPol Forum, 2023)
We characterize regional inequality in gross incomes at the municipality level in Germany using data from administrative tax returns for the period 1998-2016. More unequal municipalities are more likely to be urban and located in West Germany. Decomposing the increase in inequality in the last two decades into a between and within municipality component, we find that the increase was entirely driven by growing inequality within municipalities. Thirty years after reunification, Germany is a country with rather modest interregional inequalities but a growing level of intraregional inequality.
Keywords: 330